Effect of radiant exposure and UV accelerated aging on physico-chemical and mechanical properties of composite resins - Carlos Enrique Cuevas-Suárez; Carine Tais Walter Meereis; Norma D'accorso; Ricardo Macchi; Adriana Leticia Ancona-Meza; Eliezer Zamarripa-Calderón (University of São Paulo, 2019)
Abstract Currently, there is no consensus in terms of defining the minimum radiant exposure values necessary for achieving adequate properties of composite resin. In addition, the long-term influence that radiant exposure has on the properties of composite resins is still questionable. Objective: The objective of this study was to evaluate the effect of radiant exposure and UV accelerated aging on the physico-chemical and mechanical properties of micro-hybrid and nanofilled composite resins. Material and Methods: A nanofilled (Filtek Supreme; 3M ESPE) and a micro-hybrid composite resin (Filtek Z250; 3M ESPE) were investigated under different radiant exposures (3.75, 9, and 24 J/cm2) and UV accelerated aging protocols (0, 500, 1000, and 1500 aging hours). The degree of conversion (DC), flexural strength (FS), modulus (M), water sorption (WS), and solubility (WL) were evaluated. The results obtained were analyzed using two-way ANOVA and Tukey's test. Comparisons were performed using a significance level of α=0.05. Results: The DC, FS, and M were found to be significantly influenced by both radiant exposure and accelerated aging time. The DC and EM increased with radiant exposure in the no-aging group (0-hour aging) for both micro-hybrid and nanofilled composites, whereas no correlation was found after accelerated aging protocols. WS and WL of micro-hybrid and nanofilled composite resins were scarcely affected by radiant exposure (p>0.05), whereas they were significantly reduced by accelerated aging (p<0.001). Conclusions: Although increasing radiant exposure affected the degree of conversion and mechanical properties of micro-hybrid and nanofilled composites, no influence on the hydrolytic degradation of the material was observed. In contrast, UV accelerated aging affected both the physico-chemical and mechanical properties of the composites.